A multidisciplinary team model of caring for patients with perianal Crohn's disease incorporating a literature review, topical therapy and personal practice. Issue 2 (14th December 2012) - Garrick, Vikki; Stenhouse, Emily; Haddock, Graham; Russell, Richard K
Abstract : Background: Crohn's disease (CD) is characterised by periods of relapse and remission. Over time the disease leads almost inevitably to the complications of stricturing, penetration and fistulisation. Perianal CD involves areas of chronic abscess formation, ulceration, skin tags or fistula formation. This can be a particularly challenging and complex problem to manage, and a range of potential treatment modalities exist. Methods: This review covers the management of perianal CD and provides recommendations for practice for the multidisciplinary team (MDT), including the use of wound management products and relevant clinical images. Results: Current practice focuses predominantly on the use of antibiotic therapy, immunosuppression, immunomodulation and surgery. These therapies are used individually or in combination. The majority of evidence suggests that a combination of medical and surgical management produces the best disease outcomes. However, this treatment regime can be debilitating for the patient and compliance can be difficult. Published work on the use of topical therapy in the management of perianal CD focuses specifically on topical drug therapy; it does not, however, address the basic guiding principles of chronic wound management—in particular, optimal moisture control and the management of bacterial burden on the wound surface. Honey and silver-containing wound management products act as topical antimicrobial agents and therefore address these principles. Conclusions: Perianal CD is the archetypal condition that exemplifies the need for an MDT approach in caring for patients with inflammatory bowel disease. A combination of treatment modalities that includes topical wound management is likely to produce the best patient outcomes.